Exposure to Real Estate Losses : Evidence from the US Banks - Pinheiro, Marcelo (IMF Working Papers; Working Paper, 2009)
We implement a three-step procedure to assess the extent of exposure to real estate in commercial banks. First, we demonstrate interest rates and income to be the major determinants of delinquency. Then, we adopt a stress testing approach to calculate the impact of any adverse changes in these determinants. This suggests that a 1.3 percentage point increase in mortgage interest rate leads to a 20 percent decrease in a typical bank's distance to default. Finally, we look at the cross-sectional differences and indentify the banks with rapid loan growth along with high cost-income ratio as the most vulnerable.